Surveying the extent and wage consequences of education-labor mismatches in the Philippine labor market - Melchor, Monica Isabel Maria M.; Capuno, Joseph J. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
One of the ways in which educational outcomes are deemed successful lies in the translation of educational investments into expanded employment opportunities and higher wage outcomes. While education-skill mismatches are prevalent in both developed and developing economies, less work has been done in the developing economy context relative to the extensive analysis undertaken in developed countries, owing to data and other constraints. Amid these gaps, this paper seeks to estimate the extent of education-employment mismatches and the resulting wage consequences in the Philippine labor market. Utilizing data from the 2006 and 2012 rounds of the merged Philippine Family Income and Expenditures and Labor Force Surveys, the paper finds that as much as 38 to 39 percent of the employed individuals included in the analysis are overeducated and over a quarter of individuals are undereducated. The estimated proportion of educated and undereducated individuals varies considerably by method used. The returns to years of overeducation are estimated at 5 percent, after controlling for selection bias, as well as individual, sectoral, regional, and other factors, implying that an overeducated individual earns only 5 percent more for a surplus year of schooling relative to required years of schooling, which have returns ranging from 7 to 19 percent. Years of undereducation moreover yield returns of -4 to -10 percent. Given the wage impacts of overeducation, in particular, the results underline the importance of labor market policies targeted toward improving job-skills matching via the reduction of information asymmetries, for instance. The results moreover prompt reconsideration of public subsidies for higher education that are premised on the expectation of improved wage prospects or higher productivity of highly educated individuals, as these may not be realized in practice.
Thesis (M.A. Economics) -- University of the Philippines Diliman
Keywords: Economic development -- Effect of education on -- Philippines; Labor supply -- Effect of education on -- Philippines; Human capital -- Philippines